Development of Website-Based Emotional Intelligence Instruments as One of the Efforts to Implement Industrial Revolution 4.0 (Study on Students of SMK Muhammadiyah 1 Padang) - Fikri, Ariful; Helma, Helma; Dianto, Mori (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2022)
This research is motivated by the presence of students who are less able to manage emotions, are empty and build relationships and the absence of information technology (IT) emotional intelligence instruments, therefore researchers are interested in making website-based emotional intelligence instruments that can facilitate BK teachers in revealing intelligence. owned by students. This study aims to reveal the emotional intelligence of students at SMK Muhammadiyah 1 Padang and to design a website-based emotional intelligence instrument that is acceptable theoretically, practically and IT. This research was conducted by the method of development research (R&D). The data collection technique used is a questionnaire. The development procedure used in this study includes 5 steps, namely: 1) Potential and problems, 2) Data collection, 3) Product design, 4) Design validation, 5) Design revision, so as to produce a website-based emotional intelligence instrument final product design. The subjects in this study were 37 students of class XI TKJ and XI TBSM. The results of this study reveal that in general the emotional intelligence of students is in the moderately intelligent category, and website-based emotional intelligence instruments that have been validated by theoretical, practical, and media experts are categorized as